Research Progress and Development Trends of Materials Genome Technology - Shuling Xiong; Luohan Wang (Advances in Materials Science and Engineering)
Materials genome is a subversive frontier technology emerging in the field of international materials in recent years and also a propeller for the development of new materials. It brings fundamental changes to the traditional material research mode, aiming to accelerate the research and development of new materials and reduce costs, so as to support the development of electronic information, energy and environmental protection, aerospace, and other industries. In this paper, we introduce the strategic significance, national layout, and methods of materials genome technology and emphatically introduce the design idea and development status of materials database method. Then we summarize the development trends of materials genome and put forward suggestions for its future research, aiming to provide references for the development direction of materials genome technology in various countries, especially in developing countries.